Service Operation Strategy and Service Delivery Strategy to Enhance Business Performance - Andi Ramadhan; Sucherly; Supiansyah (Jurnal Manajemen dan Organisasi, 2022)
This study strives to investigate whether the business performance of PT Pertamina (Persero) Integrated Terminal Teluk Kabung can be improved through an effective service operation strategy and service delivery strategy. This study uses primary and secondary data information. The data analysis pulled in this study is descriptive and causal and was obtained through the census method of 104 respondents who are the owners of 136 gas stations spread across West Sumatra. The causality data was then processed using PLS-SEM software. The study results show that some gas station operators in the area complained about PT Pertamina's services to consumers, which were considered slow and inflexible. Internal processes and customer perspectives that prioritize responsiveness capabilities to market needs will potentially improve business performance sustainably.